Financing affordable urban high-rise middle-class residential property development in Malawi - Jumbe, Comfort W J M (Department of Construction Economics and Management, 2023)
Malawi's middle-class which must adapt to the experiences of liberalised housing sector, have not been able to do so due to increased exclusion in housing finance, imbalanced demand and supply forces in land resources, and disincentivised property development environment. Luckily, a strong demand for housing in Lilongwe City was for the first time met by the provision of urban high-rise residential plots. However, it remains untold if the mortgage industry will ably fund these developments and if innovative financing systems, while being successful elsewhere in the world, can do the same in Malawi. Using a mixed study approach and semi-structured questionnaires, interviews were conducted to senior real estate stakeholders. Data from primary and secondary sources under two case studies were analysed qualitatively and quantitatively using thematic analysis and descriptive statistics respectively. Key findings of the study revealed that technology-based innovations, flexible loan conditions, and appropriate legislation remain key contributors to financial institutions' inability to offer cost-reduced property loans. However, these commitments cannot be met in the short to medium terms making access to funding for affordable urban high-rise residential property developments (HRPD) impossible. Further, compromise by state organs have led to departure from prioritising HRPD in Lilongwe City as well as delayed implementation of housing subsidies, leaving the housing sector at a standstill. Finally, while it is currently illegal to crowdfund in Malawi, real estate crowdfunding (REC) has proved to be ideal for financing urban HRPD in the country as is the case in the continent. It is recommended that the state organs must start the process of making available land for urban HRPD and strengthening the land use control systems in a bid to reduce property development risks. This should be supported by unlocking subsidies and relaxing regulation to allow for REC to change the affordable housing finance landscape in Malawi.